Analisis Peran Jaksa Dalam Upaya Memulihkan Kerugian Negara Dari Kasus Korupsi - Ramadhan, Muhammad Hariyo; Pratama, Aldino Gilang; Darsono; Nasharudin; Hery Hernawan (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2022)
Because corruption is inherent in human beings as morals or morals, it is difficult to change this culture. A plan is needed to identify and address the factors driving corruption crimes. Everyone has to build good morals in themselves to deal with corruption. By violating the social and economic rights of the people, corruption has grown into an extraordinary crime. Therefore, the attempt to exterminate him should be prosecuted